Criteria for urban streets suitability for car-free day initiatives - Anteneh Afework Mekonnen (Transportation Research Interdisciplinary Perspectives)
Cities with a growing population and complexity face urban crises related to road safety and mobility. Governments and collaborative stakeholders are introducing car-free day programs to address these challenges. In this study, a scientific criterion to identify suitable streets for such programs was established through a three-round Delphi study. The study involved twenty panelists from academia, city governments, international and local organizations, and freelance consultants. The panelists identified forty-six criteria clustered into six categories through open-ended and close-ended rounds, desk research, and insights from a car-free day workshop. The panelists reached a consensus on all categories and forty items. According to the results, the panelists reached a “good agreement” on three categories, environment, health & safety, land use & roadside, and mobility & accessibility; a “moderate agreement” on the three categories, namely, categories, geometry & functionality, and policy & governance; and a “weak” agreement on the one object, namely, social & economic. The relative importance index indicated that the two categories, “mobility and accessibility” and “environment, health and safety”, were considered the most important. The study suggests that these findings can potentially influence urban planning and transportation policies.